An examination of the enhanced photocatalytic performance of PEO coatings applied on Mg alloys: A review - Arash Fattah-alhosseini; Stevan Stojadinović; Razieh Chaharmahali; Andrey Gnedenkov (Journal of Magnesium and Alloys)
There has been considerable research into the use of powdered photocatalysts for their potential to remove a range of contaminants. However, the use of photocatalytic nanoparticles in real-world applications faces several challenges, including a tendency to clump together and issues with separating and reclaiming them. Of the various strategies for securing nanoparticles to a substrate, photocatalytic coatings have emerged as a promising solution to overcome the common limitations associated with powdered forms. Coatings produced through PEO have attracted considerable interest as versatile surface treatments. They hold the potential to improve the photocatalytic efficiency of magnesium alloys. Assessments of photocatalytic activity were carried out to examine the degradation of organic dyes when exposed to both visible light and UV. The findings show that the photocatalytic performance of PEO layers is improved, a feature that can be attributed to their distinct surface structure, composition, and properties related to light absorption. This research provides a deeper understanding of the photocatalytic properties of PEO layers applied to magnesium alloys. It underscores their potential use in environmental cleanup and energy transformation applications.